Thermal and structural study of glasses in the binary system TeO2-Pb(PO3)(2) - Pereira, Camila; Santagneli, Silvia H. [UNESP]; Cassanjes, Fabia Castro; Poirier, Gael (Elsevier B.V., 2013)
The main objective of this work has been to prepare and characterize the thermal and structural properties of glasses in the pseudo binary system TeO2-Pb(PO3)(2) with respect to the composition. Homogeneous and transparent glass samples were obtained by the melt-quenching method in a large glass forming range in the pseudo binary system (100 - x)TeO2-xPb(PO3)(2) with x varying from 5 to 100. Thermal properties investigated by DSC pointed out an increase of the glass transition temperature from x 5 to x = 40 and further decrease of Tg for higher Pb(PO3)(2) concentrations. A similar tendency has been observed for the thermal stability against devitrification measured using the stability parameter Tx-Tg. FTIR together with Raman spectroscopies allowed building a structural model for these glasses with the contribution of distinct phosphate and tellurite units depending on the composition. Identification of crystalline phases obtained after the glasses heat-treatments obtained by X-ray diffraction support the structural evolution suggested by vibrational spectroscopies. These data suggest that incorporation of TeO2 in the lead metaphosphate glass results in tellurium conversion from TeO4 seesaw geometry to TeO3 trigonal pyramids and consequent conversion of well-known metaphosphate units Q(2) to modified pyrophosphate units Q(1Te)(2) in which the phosphorus PO4 tetrahedron is linked to another PO4 unit and one TeO3 pyramid. These tellurite trigonal units cross-link the modified metaphosphate chains with a resulting increase of the glass network connectivity. For high TeO2 concentrations, all Q(2) were converted to Q(1Te)(2) and the additional tellurium atoms are incorporated in the glass network as TeO4 seesaw units with a glass network built from a tridimensionalnetwork of TeO3, TeO4, and Q(1Te)(2). Finally, this work pointed out the possibility to use this pseudobinary system for the preparation of phosphate glass-ceramics containing a TeO2 crystalline phase or tellurite glass-ceramics containing a pyrophosphate or metaphosphate crystalline phase. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Glass; Lead metaphosphate; Structure; Crystallization; Tellurite